Movers Teacher Perceptions of Sensory Learning Styles and Their Implementation in Product Differentiated Learning - Helmi, Arif Mustofa; Fauziati, Endang; Muhibbin, Ahmad (Jurnal Paedagogy, 2023)
This study aims to explore the perceptions of movers of teachers towards sensory learning styles and their implementation in determining differentiated products. This research was qualitative research with a case study method. The data sources in this study were five science mover teachers in Grobogan Regency and product documents produced by students. Data collection used observation, interviews, questionnaires, and documentation—the validity of the data using triangulation of sources and techniques. The study results showed that the teacher's perception of students' sensory learning styles was relevant to their implementation in determining differentiated products. It showed that the teacher's perception was crucial in implementing differentiation learning, especially product differentiation. For this reason, teachers are needed to have the right perception of differentiated learning. The right perception will cause the implementation of differentiated learning to run effectively.